Collateral hydrogenation over proton-conducting Ni/BaZr0.85Y0.15O3−δ catalysts for promoting CO2 methanation. Issue 56 (17th September 2018) - Choi, Sungjun; Choi, Sung Min; Yoon, Kyung Joong; Son, Ji-Won; Lee, Jong-Ho; Kim, Byung-Kook; Sang, Byoung-In; Kim, Hyoungchul
Abstract : A novel steam hydrogenation process is demonstrated by applying collateral CO2 methanation over Ni/BaZr0.85 Y0.15 O3− δ, which outperforms its conventional Ni/Al2 O3 counterpart. Abstract : Despite the importance of CO2 methanation for eco-friendly carbon-neutral fuel recycling, the current technologies, relying on catalytic hydrogenation over metal-based catalysts, face technological and economical limitations. Herein, we employ the steam hydrogenation capability of proton conductors to achieve collateral CO2 methanation over the Ni/BaZr0.85 Y0.15 O3− δ catalyst, which is shown to outperform its conventional Ni/Al2 O3 counterpart in terms of CH4 yield (8% higher) and long-term stability (3% higher for 150 h) at 400 °C while exhibiting a CH4 selectivity above 98%. Moreover, infrared and X-ray photoelectron spectroscopy analyses reveal the appearance of distinct mobile proton-related OH bands during the methanation reaction.